2019
DOI: 10.1089/ten.tea.2018.0265
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 Antagonism to Treat Delayed Fracture Healing

Abstract: A significant number of fractures develop nonunion. Stem cell homing is regulated through stromal cell-derived factor 1 (SDF1) and its receptor CXCR4. Stem/progenitor cell populations can be endogenously mobilized by administering growth factors with a pharmacological antagonist of CXCR4, AMD3100, which may be a means to improve fracture healing. A 1.5 mm femoral osteotomy in Wistar rats was stabilized with an external fixator. Rats were pretreated with phosphate buffered saline [PBS(P)], vascular endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The results obtained were different from the research conducted by Meeson R et al on Wistar rats. In this study, an increase in the percentage of cartilage formation in the treatment group with a combination of G-CSF and the antagonist CXCR4 [ 36 ]. Research conducted by Herrmann et al also showed similar results, where there was an increase in the formation of cartilage areas in the G-CSF treatment compared to controls [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained were different from the research conducted by Meeson R et al on Wistar rats. In this study, an increase in the percentage of cartilage formation in the treatment group with a combination of G-CSF and the antagonist CXCR4 [ 36 ]. Research conducted by Herrmann et al also showed similar results, where there was an increase in the formation of cartilage areas in the G-CSF treatment compared to controls [ 28 ].…”
Section: Discussionmentioning
confidence: 99%